RANCANG BANGUN SISTEM INFORMASI INDUSTRI KELAPA DI PROVINSI SULAWESI UTARA BERBASIS WEB-GIS - Grentino Marcelo Durand; Dedie Tooy; Sandra E. Pakasi (Universitas Sam Ratulangi, 2019)
ABSTRACT The purpose of this research is to design and build an information system of coconut industry in North Sulawesi province by utilizing web-based Geographic Information System (GIS) and internet technology. This research was conducted to provide information of coconut industry in the web-GIS based North Sulawesi province with a wide range. This research uses the SDLC (System Development Life Cycle) method or is known as a system development lifecycle. Information system on the coconut industry in North Sulawesi province can be accessed by internet users by typing the URL in the Addressbar http://industrikelapasulut.unaux.com/. Keywords : Coconut industry. Information systems, WEB-GIS